A declining trend of methane emissions in the Los Angeles basin from 2015 to 2020. (1st March 2023) - Yadav, Vineet; Verhulst, Kristal; Duren, Riley; Thorpe, Andrew; Kim, Jooil; Keeling, Ralph; Weiss, Ray; Cusworth, Dan; Mountain, Marikate; Miller, Charles; Whetstone, James
Abstract: The Los Angeles (LA) basin was responsible for approximately 20% of California's methane emissions in 2016. Hence, curtailment of these emissions is required to meet California's greenhouse gas emissions reduction targets. However, effective mitigation remains challenging in the presence of diverse methane sources like oil and gas production fields, refineries, landfills, wastewater treatment facilities, and natural gas infrastructure. In this study, we study the temporal variability in the surface concentrations from February 2015 to April 2022 to detect a declining trend in methane emissions. We quantify the reduction due to this declining trend through inverse modeling and show that methane emissions in the LA basin have declined by 15 Gg, or ∼7% over five years from January 2015 to May 2020.